Desain Aplikasi Pelayanan Keluhan Pelanggan Icon+ Berbasis Mobile Pada PT. Indonesia Comnet Plus SBU Palembang - Apriansyah Apriansyah; Zulhipni Reno Saputra; Al Amalul Khoir (Jurnal Ilmiah Informatika Global, 2022)
Along with the increasing number of internet service users at PT Indonesia Comnets Plus (ICON+), the number of customer complaints about the services received also increases. At this time PT. Indonesia Comnets Plus (ICON+) still does not have a system that accommodates customer complaints. Therefore, the author focuses on the purpose of this study to design a Customer Complaint Service Application design for PT. Indonesia Comnet Plus (ICON+) Palembang branch. The customer complaint application at PT Indonesia Comnets Plus (ICON+) is designed using the UML (Unified Modeling Language) tool which is used to describe the system designed and to make it easier to visualize the system designed by the author. This application is designed using Figma to design the user interface. Meanwhile, to design the database design the author uses a sqlite database. The research method applied in this research is the development of the waterfall method which describes a systematic and sequential approach (step by step) in software development. (ICON+). Where customers can submit complaints through this application without having to come directly to the ICON + Office to be more effective and time and cost efficient. As for PT PT Indonesia Comnets Plus (ICON+) this application can provide convenience in managing customer complaints related to services that are being used by PT Indonesia Comnets Plus (ICON+) customers so that they can be handled properly.Keywords : ICON+, Design, Mobile, UML, Waterfall